A Dilemma for Higher-Level Suspension. Issue 4 (2022) - TAL, EYAL
Abstract: Is it ever rational to suspend judgment about whether a particular doxastic attitude of ours is rational? An agent who suspends about whether her attitude is rational has serious doubts that it is. These doubts place a special burden on the agent, namely, to justify maintaining her chosen attitude over others. A dilemma arises. Providing justification for maintaining the chosen attitude would commit the agent to considering the attitude rational—contrary to her suspension on the matter. Alternatively, in the absence of such justification, the attitude would be arbitrary by the agent's own lights, and therefore irrational from the agent's own perspective. So, suspending about whether an attitude of ours is rational does not cohere with considering it rationally preferable to other attitudes, and leads to a more familiar form of epistemic akrasia otherwise.